The effect of high intensity interval training along with consumption of caraway seeds (Carum carvi L.) on liver enzymes, lipid profile, and blood glucose in obese and overweight women - S Ghorbani; R Alizadeh; L Moradi (فصلنامه ابن سینا)
Background: In the recent years, interest to the assessment of medicinal plants on the protection of body has emerged. The aim of this study was to investigate the effect of high intensity interval training (HIIT) along with consumption caraway seeds on liver enzymes, lipid profile and blood glucose in obese and overweight women. Materials and methods: In this semi-experimental study, 24 women aged 25 to 35 years were selected and randomly divided into three obese, overweight, and control groups. All groups consumed caraway seeds (powder), 50 mg/kg twice a day for six weeks. The test group performed three HIIT sessions per week for six weeks. Each session consisted of four to six repeats of maximal sprint running (90-95% of maximum heartbeat) within a 20m area with 60s recovery gaps. Blood samples were obtained after 12 hours fasting before and after training. Data were analyzed using ANOVA with repeated measure for assessment of time interactive effect (consisting of two levels, i.e. before and after training) on the studied groups in the applied amounts of the desired variables. Results: The results of the current study showed that the three groups have significant differences in term of triglyceride (p=0.043) and AST (p=0.005) factors, but no significant difference was observed in the other variables (FBS, cholesterol, ALT, ALP, and ALT/AST) between the groups. Conclusion: According to the results of this study, it seems that HIIT with consumption of caraway seeds can be useful in prevention from the occurrence of some diseases associated with obesity; however, to achieve the desired results, the intervention should be longer.